2018
DOI: 10.21649/akemu.v24is.2574
|View full text |Cite
|
Sign up to set email alerts
|

Visual Inspection with Acetic Acid-an Acceptable Option in Screening of Cervical Cancer.

Abstract: Objectives| To evaluate the accuracy of Visual Inspection with Acetic Acid (VIA) and Papanicolaou (Pap) smear as screening tests for cervical carcinoma and compare it with cervical biopsy as a gold standard. Methods| This was a cross-sectional study conducted at Gynae Unit 3 Services Institute of Medical Sciences from Jan 2016 to December 2016. All the married patients between 18 to 64 years of age were included in the study. Every patient underwent VIA, Pap smear and colposcopic directed biopsy from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Recently a study conducted by Aslam S. et al 2018 in Services Institute of Medical Sciences showed that among Visual Inspection with Acetic Acid (VIA) and Papanicolaou (PAP) smear as compared to gold standard cervical biopsy. Acetic Acid (VIA) showed better screening as compared to PAP smear with sensitivity of 97.67% and specificity of 84.29% with overall accuracy of 85.5%.Specificty could be increased by combing the PAP smear with VIA screening 13 This research paper investigates the present level of awareness, attitude, and knowledge of Pakistani medical students and doctors towards cervical cancer screening, and identifies factors that influence their attitude to and uptake of cervical cancer screening. It is researcher's perception that a knowledge full Health professional can emphasize and educate the patients more effectively, as also suggested by literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a study conducted by Aslam S. et al 2018 in Services Institute of Medical Sciences showed that among Visual Inspection with Acetic Acid (VIA) and Papanicolaou (PAP) smear as compared to gold standard cervical biopsy. Acetic Acid (VIA) showed better screening as compared to PAP smear with sensitivity of 97.67% and specificity of 84.29% with overall accuracy of 85.5%.Specificty could be increased by combing the PAP smear with VIA screening 13 This research paper investigates the present level of awareness, attitude, and knowledge of Pakistani medical students and doctors towards cervical cancer screening, and identifies factors that influence their attitude to and uptake of cervical cancer screening. It is researcher's perception that a knowledge full Health professional can emphasize and educate the patients more effectively, as also suggested by literature.…”
Section: Introductionmentioning
confidence: 99%